Electrospun Fibrous Scaffolds for Tissue Engineering: Viewpoints on Architecture and Fabrication - Jun, Indong; Han, Hyung-Seop; Edwards, James R.; Jeon, Hojeong (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
Electrospinning has been used for the fabrication of extracellular matrix (ECM)-mimicking fibrous scaffolds for several decades. Electrospun fibrous scaffolds provide nanoscale/microscale fibrous structures with interconnecting pores, resembling natural ECM in tissues, and showing a high potential to facilitate the formation of artificial functional tissues. In this review, we summarize the fundamental principles of electrospinning processes for generating complex fibrous scaffold geometries that are similar in structural complexity to the ECM of living tissues. Moreover, several approaches for the formation of three-dimensional fibrous scaffolds arranged in hierarchical structures for tissue engineering are also presented.